POST-INDUSTRIAL URBAN AREAS IN THE CONTEXT OF RUINATION, DEMOLITION AND URBAN REGENERATION IN A POST-SOCIALIST CITY: EXPERIENCES OF ŁÓDŹ, POLAND - Kazimierczak, Jaroslaw (2019)
Since the beginning of 1990’s Łódź has become one of the largest and the fastest shrinking cities in Poland and Central-Eastern Europe (Jaroszewska & Stryjakiewicz, 2014). This is the result of political transformation in Poland at the turn of the 1980’s and 1990’s, which caused the collapse of Łódź economy based on textile industry monoculture. The radical population change has triggered highly dynamic transformations in Łódź urban fabric and produced numerous ruins, voidances, not used houses and dwellings, abandoned and vacant land in a contemporary city, especially in its central, historical districts. Furthermore, one of the key role in the process of ruination of Łódź 19th-century urban tissue played the communists who ruled the city without any respect to its urban heritage for almost 50 years from the end of World War II. That was an intentional and ideologically motivated policy. In contrast, new capitalist circumstances of urban development in Poland since political and economic transformation in 1989 have freed private property developer’s ”game of urban space” that has strengthened urban sprawl and decapitalization of historical, especially post-industrial buildings in Łódź downtown. The aim of our research is to identify qualities of post-industrial urban areas in the downtown of Łódź in the period of 1989-2016 and then the role of ruined and abandoned post-industrial buildings in urban regeneration process.